1984
DOI: 10.1126/science.6701530
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Arteries of Cardiac Patients Are Hyperreactive and Contain Stores of Amines: A Mechanism for Coronary Spasm

Abstract: Coronary arteries from hearts of cardiac patients contain significantly higher concentrations of histamine than do those from noncardiac patients. The coronary vessels of cardiac patients are also hyperresponsive to histamine and serotonin. These differences between groups of patients suggest an explanation for coronary artery spasm in heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
1
2

Year Published

1992
1992
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(90 citation statements)
references
References 12 publications
3
84
1
2
Order By: Relevance
“…Increased histamine concentration in cardiac tissue also corresponds to increased mast cell density [16]. In clinical situations, the presence of mast cells around and within the coronary blood vessels has been implicated in the pathophysiology of coronary artery disease [31][32][33]. The role of mast cells has been established in myocardial fibrosis in Africans [18], and in dilated cardiomyopathy secondary to systemic sclerosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Increased histamine concentration in cardiac tissue also corresponds to increased mast cell density [16]. In clinical situations, the presence of mast cells around and within the coronary blood vessels has been implicated in the pathophysiology of coronary artery disease [31][32][33]. The role of mast cells has been established in myocardial fibrosis in Africans [18], and in dilated cardiomyopathy secondary to systemic sclerosis [34].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that the mast cell content of unstable plaques is increased compared with stable plaques (Kaartinen et al, 1998). Histamine is released from mast cells during myocardial ischemia (Frangogiannis et al, 1998) and is found in significantly higher levels (two-fold increase) in coronary arteries from patients who died from coronary heart disease compared with controls (Kalsner and Richards, 1984).…”
Section: Tg In Atherosclerosismentioning
confidence: 99%
“…Histamine and other mast cell mediators are known to regulate vasodilation and bronchoconstriction (1,2), and to modulate the functions of other cell types, including monocytes and macrophages (3,4), eosinophils (5,6), T lymphocytes (7), neutrophils (8), and endothelial cells (9). A direct association between mast cell-derived histamine and vascular inflammation is evident from the finding that the coronary arteries of patients with ischemic heart disease contain more mast cells and histamine than normal vessels (10), and patients with variant angina have elevated levels of histamine in the coronary circulation (11). The fact that histamine is able to stimulate endothelial cell production of such proinflammatory cytokines as IL-6 and IL-8 (9,12,13) indicates that this mast cell product can act as an important inflammatory agent in addition to its well-recognized vasoactive functions.…”
mentioning
confidence: 99%